2020
DOI: 10.1371/journal.pone.0236638
|View full text |Cite
|
Sign up to set email alerts
|

A global meta-analysis of livestock grazing impacts on soil properties

Abstract: Grazing effects on soil properties under different soil and environmental conditions across the globe are often controversial. Therefore, it is essential to evaluate the overall magnitude and direction of the grazing effects on soils. This global meta-analysis was conducted using the mixed model method to address the overall effects of grazing intensities (heavy, moderate, and light) on 15 soil properties based on 287 papers published globally from 2007 to 2019. Our findings showed that heavy grazing significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 56 publications
(84 reference statements)
4
58
0
Order By: Relevance
“…Lai and Kumar [40] (2020) analysed 287 papers about grazing impacts on soil properties from 2007 to 2019. They found that heavy and moderate grazing both caused a significant increase in bulk density and penetration resistance and a decrease in soil organic carbon and total nitrogen content in the 0-10 cm layer.…”
Section: Recent Review Papers On the Subjectmentioning
confidence: 99%
“…Lai and Kumar [40] (2020) analysed 287 papers about grazing impacts on soil properties from 2007 to 2019. They found that heavy and moderate grazing both caused a significant increase in bulk density and penetration resistance and a decrease in soil organic carbon and total nitrogen content in the 0-10 cm layer.…”
Section: Recent Review Papers On the Subjectmentioning
confidence: 99%
“…Cattle grazing impacts on soil compaction, soil organic carbon, total nitrogen, and available potassium were greater than sheep grazing. Dahal et al [40] demonstrated that strategic grazing reduced nitrate runoff, whereas Schon et al [41] reported that proper grazing pressures increase earthworm populations.…”
Section: Soil Quality Studies Focusing On Grazed Pasturesmentioning
confidence: 99%
“…The University Missouri Soil Health laboratory will perform the following health parameters: (i) total nitrogen and potentially mineralizable nitrogen, (ii) wet aggregate stability and bulk density, (iii) total organic carbon and active carbon, and (iv) phospholipid fatty acids. Perennial pastures may support soil health by (i) reducing erosion, (ii) accumulating soil organic matter, (iii) increasing macro and micropore space, and (iv) increasing the potential water availability for plant growth and development [39][40][41]. Moving cattle frequently, maintaining soil surface residue, avoiding grazing when soils are wet, and providing plant recovery after grazing are attractive attributes of a viable grazing program.…”
Section: Positioning Grazing Management To Support Long-term Soil Health Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Grazing, as a component of land use, is associated with certain patterns in hydrosedimentary conditions from event-scale to the catchment scale (e.g., Bartley et al, 2007;Rodriguez-Lloveras et al, 2015) and several studies have analyzed the relationship between unsustainable grazing, grassland status, and animal types (e.g., Warren et al, 1986;Mwendera and Saleem, 1997;Meyles et al, 2003;Pande and Yamamoto, 2006;Kidron, 2016;Pulley and Collins, 2019;Lai and Kumar, 2020). Unsustainable and prolonged grazing may trigger hydrological changes such as soil water content, but also the activation of runoff with an impact on the streamflow regime (e.g., maximum and minimum flow) affecting runoff coefficients (Gifford and Hawkins, 1978;Gifford et al, 1983;Markart et al, 2006;Sadeghi et al, 2007;Ruggenthaler et al, 2015), even with modifications of the terrestrial water (Vörösmarty and Sahagian, 2000).…”
Section: Introductionmentioning
confidence: 99%